PENGARUH NPL, CAR, LDR, DAN ROA TERHADAP CKPN PERUSAHAAN DI SUBSEKTOR PERBANKAN - Parman, Yuni; Nugroho, Vidyarto (Jurnal Paradigma Akuntansi, 2025)
This research was conducted with the aim to determines the effect of Non-Performing Loans (NPL), Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Return on Assets (ROA) on Allowance for Impairment Losses (CKPN) of commercial banks listed on Indonesia Stock Exchange (IDX) from 2019 to 2021. The sample was selected using a purposive sampling technique and valid final data of 43 commercial banks was obtained. The data then processed using multiple linear regression analysis assisted by the 26th version of IBM SPSS (Statistical Product and Service Solution) program and Microsoft Excel 2019. The findings show that NPL and ROA have an effect on CKPN while CAR and LDR have no effect on CKPN. The implication of this research is the need for the establishment of CKPN based on relevant assessment indicators to mitigate the risk of impairment losses on productive assets in order to maintain the well-being of banks which will be a positive signal for investors.